HYDROGEN IN SOME NATURAL GARNETS STUDIED BY NUCLEAR REACTION ANALYSIS AND VIBRATIONAL SPECTROSCOPY - Maldener J.; Rauch F.; Hösch A.; Langer K. (My University, 2003)
A suite of 11 gem-quality, optically completely clear garnet crystals with a broad variety of compositions in the space of the end members pyrope-almandine-spessartine-grossular-andradite-goldmanite were analyzed for trace amounts of "water" by nuclear reaction analysis, NRA, based on the reaction 1H(15N, αγ)12C, and by single-crystal absorption spectroscopy in the vOH vibrational range using microscope-FTIR-spectroscopic methods. The aim was to establish a calibration of the highly sensitive IR method with high areal resolution for "water" determination in garnets, by studying garnets of a wide compositional range, and to check for compositional dependencies of the integral molar absorptivities of the "water" component, εint [1mol-1H20cm-2], in the nominally "water"-free garnets. The results of NRA show a broad variation of water contents in the range (14 3) to (950 ± 80) wt ppmH2O, the values being low and very high for the garnet solid solutions (PyrAlm)ss and close-to-end-member GrossSS, respectively. There were no indications of inhomogeneities in the OH distribution, except possibly for one of the garnets (grossular, variety hessonite, from Tanzania). The quantitative evaluation of the complex vOH spectra, which showed similar shape only for members of the (PyrAlm)ss, yielded integral absorption coefficients, αint (cm-2), which allowed the calculation of integral molar absorptivities, εint, using the "water" values of NRA. The εint values obtained varied in a wide range but with no obvious correlation with the composition of the garnet except for the extremely high values, in the 104 range, of the two specimen with compositions close to end-member grossular. In all other garnets, εint was in the 103 range with an average of εint = 3630 ± 1580[1mo1-1H2Ocm-2]. Therefore, this value is proposed for the use in routine "water" determinations of compositionally different garnets by the micro-IR method, except for garnets near to end-member grossular.
Keywords: Determination of hydrogen in garnets; Nuclear reaction analysis of hydrogen; Calibration of the IR-determination of hydrogen in garnets